2007
DOI: 10.1186/1749-8546-2-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular biology of cantharidin in cancer cells

Abstract: Herbal medicine is one of the forms of traditional medical practice. Traditional Chinese medicine (TCM) and traditional Vietnamese medicine (TVM) are well-known for their long-standing tradition of herbal medicine.Secreted by many species of blister beetle, most notably by the 'Spanish fly' (Lytta vesicatoria), cantharidin inhibits protein phosphatases 1 and 2A (PP1, PP2A). Blister beetle has been used in Asian traditional medicine to treat Molluscum contagiosum virus (MCV) infections and associated warts, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 80 publications
2
63
0
3
Order By: Relevance
“…On the other hand, the antiapoptotic protein Bcl-2 expression was decreased. It is reported that increase in the generation of cellular reactive oxygen species induces cell cycle arrest and apoptosis [18,19]. Results from the current study showed that incubation of HCT-15 cells with capecitabine led to increase in the production of reactive oxygen species.…”
Section: Discussionsupporting
confidence: 50%
“…On the other hand, the antiapoptotic protein Bcl-2 expression was decreased. It is reported that increase in the generation of cellular reactive oxygen species induces cell cycle arrest and apoptosis [18,19]. Results from the current study showed that incubation of HCT-15 cells with capecitabine led to increase in the production of reactive oxygen species.…”
Section: Discussionsupporting
confidence: 50%
“…The nature and pattern of the mutations suggest that PPP2R1A functions as an oncogene (37). Cantharidin has potent anticancer activity on many types of human cancer cells (38,39) and is used in traditional Chinese and Vietnamese medicine for cancer treatment (40). LB-100 (Lixte), a novel PP2A inhibitor with low toxicity, enhances the effect of cancer chemotherapy by blocking DNA damage-induced defense mechanisms (41).…”
Section: Discussionmentioning
confidence: 99%
“…28 CTD was previously reported to induce apoptosis in several kinds of cancer cells. 3,7 Based on the cell-cycle analysis, we further characterized CTD/CTD-NSVs induced apoptosis by Hoechst 33342 staining. As shown in Figure 4, MCF-7 cell nuclei were round and homogeneously stained in control and blank NSV groups; however, after being treated with 20 µM CTD for 48 hours, cells showed marked nuclei condensation.…”
Section: Cell-apoptosis Observationmentioning
confidence: 99%
“…1 These dried insect bodies are traditionally employed in the People's Republic of China to treat warts and mollusca through topical administration. 2,3 Cantharidin (CTD), the major bioactive compound in Mylabris, exists in all body fluids, and its antitumor activity has been long acknowledged. 2 The potential of CTD has been thoroughly elucidated, and its antitumor effect is considered primarily due to its potently and selectively inhibitive ability on serine/threonine protein phosphatases 1 and 2A.…”
Section: Introductionmentioning
confidence: 99%